PERTENTANGAN DAN KESADARAN KELAS DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER (PENDEKATAN TEORI MARXIS) - Risnawati Risnawati; Anshari Anshari; Aslan Abidin (Universitas Negeri Makassar, 2016)
Abstract. Class Antagonism and Class Consciousness In Novel Human Earth Works Pramoedya Ananta Toer (Marxist Theory Approach). The purpose of this study was to: (1) Describe the picture of class conflict in the novel Earth of Mankind by Pramoedya Ananta Toer. (2) Describe the class consciousness of the Earth Novel Human Pramoedya Ananta Toer. The method used in this research is descriptive qualitative method. The data used in this study a sentence or paragraph that contains a picture of class conflict and class consciousness that is present in Earth's novel Man Pramoedya Ananta Toer. Data collected by reading techniques and note techniques. Based on this analysis we can conclude several things, namely: (1) the class antagonism is one form of fraud against human values, because in it there is oppression, deprivation, injustice and lack of freedom the Proletariat. The bourgeoisie has caused many problems of humanity. The conflict that led to the conflict between Native people are Nyai Ontosoroh as the Proletariat by Europeans as the bourgeoisie. (2) Nyai and Minke has been trying hard to fight against the bourgeoisie. However, not all desirable things can be owned and not all desired can be realized even with maximum effort. A struggle not only be seen from the results, but can be seen as a long process that forms an inner personality.